2021
DOI: 10.1177/23259671211011510
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport After Bone–Patellar Tendon–Bone Autograft ACL Reconstruction in High School–Aged Athletes

Abstract: Background: Anterior cruciate ligament (ACL) injuries are occurring with increasing frequency in the adolescent population. Outcomes after ACL reconstruction (ACLR) are inconsistently reported in homogeneous patient populations. Purpose/Hypothesis: To evaluate outcomes after bone–patellar tendon–bone (BTB) autograft ACLR in competitive high school–aged athletes by examining return to sport (RTS), patient satisfaction, and reinjury rates. Our hypothesis was that RTS rates and satisfaction will be high and reinj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…The timing of RTP after ACL‐R using BPTB autograft (9.7 months) was significantly earlier than that using HT autograft (10.5 months). These results were similar when compared with previous studies evaluating RTP among athletes [17, 25, 34]. Irvine et al [18] indicated that the timeline for graft healing has implications for RTS.…”
Section: Discussionsupporting
confidence: 87%
“…The timing of RTP after ACL‐R using BPTB autograft (9.7 months) was significantly earlier than that using HT autograft (10.5 months). These results were similar when compared with previous studies evaluating RTP among athletes [17, 25, 34]. Irvine et al [18] indicated that the timeline for graft healing has implications for RTS.…”
Section: Discussionsupporting
confidence: 87%
“…2,24,32,38,41 A further difference between the current study and others is that all patients in the current study received a hamstring tendon graft, whereas the populations in other studies received a mix of both hamstring tendon and patellar tendon grafts. 4,12,17,22 When studying a cohort of 53 similarly young patients who had undergone ACL reconstruction with a patellar tendon graft, Rauck et al 31 reported a graft rupture rate of 7.4%, which is not dissimilar to the finding of the current study. It is not clear whether their patients underwent strength testing.…”
Section: Discussionsupporting
confidence: 56%
“…The authors reported that the soccer players were able to RTP following a period of between 6.1 and 11.1 months. However, even though 8.7 months represents a significant period of absence from soccer matches, the recovery time highlighted in this research is considerably shorter compared with studies performed on samples of NFL [51,52], NBA [24], schoolaged [53], amateur [54], and recreational athletes [55]. For instance, RTP times of 9.8 [24] and 12.6 [52] months were recorded for NBA and NFL players, respectively.…”
Section: Rtp After Aclr In Soccer Playersmentioning
confidence: 57%